Analysis of the distribution of microhardness, mineral, and organic content of human, bovine, and ovine teeth - Degrazia, Felipe Weidenbach (2023)
Objetive. Human teeth have been commonly used for in vitro and in situ studies. Currently, other animals’ teeth have been purposed for dental research to overcome human teeth’ problematic availability. This study aimed to investigate the enamel and dentin from human, bovine, and ovine teeth concerning the microhardness, organic, and inorganic contents via micro-Raman spectroscopy. Methods. Human, bovine, and ovine teeth were divided according to their type and age into seven groups: Ovine; Bovine-12 months; Bovine-24 months; Bovine-36 months; Bovine-48 months; Bovine-+60 months; Human (control). The enamel’s microhardness (superficial and deep) and dentin (superficial, middle, and deep) were analyzed. The calcium/phosphate ratio and amide contents were determined by micro-Raman spectroscopy. Results. Overall, the microhardness of human enamel was superior to the other species. Dentin’s microhardness was similar among groups. Ovine group showed lower values of calcium/phosphate ratio than human. Amide content was similar between bovine and human. The microhardness and calcium/phosphate ratio of enamel and dentin, respectively, decreased as the age of bovine teeth increased. Conclusions. Researchers must be aware and take into consideration the differences of ovine and bovine enamel compared to human enamel. Other alternatives that are more similar to the microhardness of human enamel should be sought. Bovine teeth of 12 and 24 months are suitable substitutes for dentin of human teeth. Researchers must also be aware of the age of the animals and specify it in the studies.